Pengaruh Persepsi Harga dan Promosi Terhadap Keputusan Pembelian Melalui Platform E-Commerce Tiktok Shop di Jakarta Timur - Kristian; Cori, Catarina (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
This study aims to a) see the effect of Price Perception on Purchasing Decisions through the TikTok Shop e-commerce platform in East Jakarta. b) see the effect of Promotion on Purchasing Decisions through the TikTok Shop e-commerce platform in East Jakarta and c) obtain an overview of the magnitude of the influence of Price Perception and Promotion on Purchasing Decisions through the TikTok Shop e-commerce platform in East Jakarta. The research method uses a descriptive method with a quantitative approach. Sampling in this study uses the accidental sampling technique or incidental sampling, namely the technique of determining samples based on coincidence Where, anyone who happens to meet the researcher and is considered suitable to be a data source will be used as a sample. The number of samples in this study was 96 respondents. Based on the results of the study, it can be concluded as follows: The results of the hypothesis test show that price perception has a significant effect on purchasing decisions through the TikTok Shop platform in East Jakarta, with a price perception contribution of 58.5%. Other factors not discussed in the study contribute 41.5%. b) The results of the hypothesis test show that promotion significantly influences the decision to purchase through the TikTok Shop e-commerce platform in East Jakarta, through a promotion contribution of 74.9%. Other factors not discussed in the study contribute 25.1%. c) According to the results of the hypothesis test, it shows that price perception and promotion simultaneously influence the significance of the decision to purchase through the TikTok Shop e-commerce platform in East Jakarta, with the contribution of price perception and promotion variables to customer satisfaction of 75.7%, while the last 24.3% comes from additional components not discussed in this study